Fabrication and Deformation of 3D Multilayered Kirigami Microstructures. Issue 11 (29th January 2018) - Humood, Mohammad; Shi, Yan; Han, Mengdi; Lefebvre, Joseph; Yan, Zheng; Pharr, Matt; Zhang, Yihui; Huang, Yonggang; Rogers, John A.; Polycarpou, Andreas A.
Abstract: Mechanically guided 3D microassembly with controlled compressive buckling represents a promising emerging route to 3D mesostructures in a broad range of advanced materials, including single‐crystalline silicon (Si), of direct relevance to microelectronic devices. During practical applications, the assembled 3D mesostructures and microdevices usually undergo external mechanical loading such as out‐of‐plane compression, which can induce damage in or failure of the structures/devices. Here, the mechanical responses of a few mechanically assembled 3D kirigami mesostructures under flat‐punch compression are studied through combined experiment and finite element analyses. These 3D kirigami mesostructures consisting of a bilayer of Si and SU‐8 epoxy are formed through integration of patterned 2D precursors with a prestretched elastomeric substrate at predefined bonding sites to allow controlled buckling that transforms them into desired 3D configurations. In situ scanning electron microscopy measurement enables detailed studies of the mechanical behavior of these structures. Analysis of the load–displacement curves allows the measurement of the effective stiffness and elastic recovery of various 3D structures. The compression experiments indicate distinct regimes in the compressive force/displacement curves and reveals different geometry‐dependent deformation for the structures. Complementary computational modeling supports the experimental findings and further explains the geometry‐dependent deformation. Abstract : 3D multilayered kirigami microstructures are mechanically driven using compressive buckling of 2D precursor patterns, consisting of multilayer thin membranes. In situ scanning electron microscopy flat punch compression reveals high flexibility and recoverability of about 100% height compression. The deformation modes are observed to be geometry‐dependent. Computational modeling supports the experimental results, and provides insights on the stress/strain induced on each layer.